THE BLOOD LEYKOGRAMA OF RABBITS AT TOTAL X-RAY IRRADIATION ON A BACKGROUND THE PYRIDOXINE ACTION - Kostіuk S.S. (World of Medicine and Biology, 2014)
The study was conducted the influence of X-ray irradiation of rabbits on the percentage of the various forms of peripheral blood leukocytes with the use of pyridoxine as radioprotective. It is found that the total exposure of rabbits by X-rays caused an increase in the leucocyte count psevdoeosinophills percent, especially rod-shape nucleuses, the emergence of young and myelocytes and a decrease in lymphocytes. In the experimental group of the rabbits, used pyridoxine, these figures were much closer to normal.